Development banks - Diamond, William (Baltimore, Maryland : John Hopkins, 1957)
This publication was out to discuss practical problems in banking system and to proffer solutions or best approach to cushion the effects of the existing challenges.
Includes bibliographic references and index.
asm 24/01/2019
Loans
Keywords: Development banks; Investment banking; Economic development; Developing countries